Influencia de la satisfacción con la vida y la satisfacción laboral en el rendimiento : una aproximación experimental - Arrué García, Italo Carlos (2015)
Job performance has been the most important study object in the Human Resources scope, due to its direct impact on productivity and quality of work nowadays. Parallelly, job satisfaction and subjective well-being (SWB) have been studied as variables that boost job performance. Nowadays, consistent correlational evidence exists, which presents life satisfaction –component of SWB– as an element that is more related to performance than job satisfaction itself. However, there are not sufficient experimental researches that confirm specific causal relationships among these variables. In the present study, a comparison between job satisfaction and life satisfaction has been made, as variables that positively affect job performance; and results report that life satisfaction exerts a greater positive influence over performance than job satisfaction does. Consequently, it can be asserted that social sciences may be approaching to a new potential predictor of job performance, the one that had not been considered for a long time: Satisfaction with life.